Latin America: freedom of information in the line of fire - Gómez Montano†, Alicia (2021)
This text takes up the conference given by the journalist and former vice-president of Reporters without Borders-Spain, Alicia Gómez, during the Study Day “Violence, journalism and fundamental freedoms in Latin America (XX-XXI)”, in Chambéry, France, in September 2019. The general role of the organization Reporters Without Borders in its defense of journalism and freedom of expression, as well as the support and protection that RSF provides to media professionals is highlighted at first. The author takes stock of the various obstacles faced by journalists in evoking the situation of press freedom in Latin America and highlights authoritarianism and misinformation as some of the ills affecting the region. She also mentions recent cases of violence against journalists in Latin American countries and underlines the impact that the different actions of political and/or criminal groups have on the informative work, causing in some cases self-censorship, exile and even death.